Comparative studies of antigen 21 in Mycobacterium and Nocardia species: possible taxonomic relationships with Mycobacterium leprae. - Widebäck, K (1980)
Studies of Mycobacterium leprae, Mycobacterium tuberculosis and Nocardia caviae in comparison with each other and with other Mycobacterium and Nocardia species were performed on the basis of antigen 21 intramolecular heterogeneity. Three different antisera were used: rabbit anti-Mycobacterium smegmatis antiserum, rabbit anti-Nocardia asteroides antiserum, and a lepromatous serum pool. With reference to each of the three antiserum sources used the strains were ranked in an order of relatedness or sharing of determinants. The three antisera showed distinctly different antigen 21 antibody specificities reflecting the species origin of the immunogen. The present investigations confirmed that antigen 21 of N. caviae shares determinants with antigens from Mycobacterium strains which were not present in corresponding antigens of all other Nocardia strains tested. M. tuberculosis, as judged by antigen 21 analysis, occupies a position separate from both the slow-growing and the fast-growing mycobacterial clusters in accordance with accepted taxonomic relationships. An interesting possibility of establishing a position for M. leprae in relation to other mycobacterial species was apparent. The order of relatedness among the strains studied went from M. leprae to M. tuberculosis to N. caviae to Mycobacterium avium to Mycobacterium fortuitum, the last two being representatives of the slow-growing and fast-growing mycobacteria. It can therefore be concluded that evidence from antigen 21 analysis indicates that M. leprae is more closely related to M. tuberculosis than to the other strains investigated.